Meningoencephalitis by Cryptococcus. Case presentation - Idalmis Reyes Rodríguez; María Odeymi Urdanivia Cruz; Mavis Pórtela Sánchez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
Cryptococcus neoformans is a yeast-capped fungus, with marked neurotropism; it is the causal agent of cryptococcosis, deep fungal infection, of sub-acute or chronic course, considered as opportunistic. Cryptococcal meningitis presents distinctive clinical characteristics. In most cases it is acquired out of the hospital and develops sub acutely. If it is not treated it can be fatal in a few weeks. For these reasons it was decided the publication of this case of a 60 year old female patient who was brought to the Gustavo Aldereguía Hospital in Cienfuegos, with headache and loss of consciousness. On questioning there was information of a personal antecedent of headaches without apparent cause for some time ago. She was admitted conscious at the ICU. Some tests were performed, among them, microbiological study of cerebrospinal fluid and blood culture samples were taken , according to the standards established , were Cryptococcus neoformans was isolated. Unfortunately after having been diagnosed the patient died.